Human Resource Management (HR) To Maintain The Quality Of Education - Ading Rahman Sukmara (SEAN Institute, 2024)
According to human resource management, members are important resources that contribute to the achievement of organizational goals. It must be used fairly and efficiently for the benefit of individuals, communities, and organizations. The purpose of this study is to provide a description and interpretation of existing data as part of descriptive research that focuses on facts (fact finding) of a problem or condition . Human resource management improves the quality of education by regulating recruitment, selection, placement, training, compensation, job security, career development, and retirement. Data for descriptive qualitative analysis were collected through observation sheets. Human resource management focuses on things like planning, recruitment, selection, placement, work performance, training, salary, production safety, career development, work relations, retirement, and improving the ability of the teaching team. This study shows that school residents can be more motivated to work because of human resource management. The researcher hopes that the findings of this study will help other researchers in conducting human resource research.